Why and How Chinese Non-Financial Firms Hedge? An Empirical Study on the Determinants and Effects of Corporate Hedging - Li, Qiaoqiao (2017)
With the internationalisation of RMB and the acceleration of the opening of Chinese financial market, Chinese companies face more foreign exchange exposure and default risk, which require more effectively risk management strategy. Given the significant role of derivative instruments in mitigating risks, this research investigates why and how Chinese firms hedge by employing a unique hand-collected dataset which includes a sample of 501 Chinese mainland and Hong Kong non-financial firms listed in Hong Kong Stock Exchange from 2008 to 2016. To answer the question of how Chinese companies hedge, this study firstly summarises the statistics of sample Chinese firms’ hedging activities. Then, the association between the likelihood of hedging and firm’s characteristics is estimated by univariate and multivariate logit analysis. Afterwards, this dissertation studies the role hedging with derivatives plays in Chinese companies’ risks and values. The main findings of this research are as follows. Firstly, the results suggest that the most popular derivatives in China is foreign exchange derivatives. Apart from using financial derivative instruments to manage financial risks, both Hong Kong and Chinese mainland corporations also use foreign debt as natural hedging. Secondly, larger Chinese companies and enterprises with more foreign exchange exposures are more willing to hedge than other firms. Firms with high profitability might tend to hedge as well. Thirdly, hedging strategy reduces firm’s equity risk and the likelihood of default. And it slightly increases the value measured by Tobin’s Q without improving the profitability. This contrary effect of hedging on firm’s value and profitability might indicate that hedging improves the value of firms by reducing risks, not by improving the financial performance. Overall, Chinese firms may adopt derivatives mainly for hedging not for speculative purposes.